Comparison of Dilapan-S and laminaria for cervical priming before surgical pregnancy termination at 17–22 weeks' gestation - Chambers DG; Willcourt RJ; Laver AR; Baird JK; Herbert WY (Dove Medical Press, 2011)
Dennis G Chambers, Robin J Willcourt, Anthony R Laver, Jane K Baird, Wye Y HerbertThe Queen Elizabeth Hospital Pregnancy Advisory Centre, Woodville Park, Adelaide, South Australia, AustraliaMethods: A retrospective analysis of medical records of three consecutive cohorts of women. All cohorts received a digoxin feticide injection on Day 1. Two cohorts were treated with laminaria, cohort A of 151 women over 1–2 days and cohort B of 52 women over 1–3 days, and cohort C of 151 women was treated with Dilapan-S over 1–3 days.Results: Adequate cervical priming for dilatation and evacuation (D&E) on Day 2 was achieved in 98% of the Dilapan-S cohort and 56% of cohort A and 40% of the cohort B laminaria cohorts. Return to theater for D&E 3–4 hours after dilator insertion on Day 2 occurred in 62.3% of Dilapan-S cohort C and 9.3% of cohort A and 4% of cohort B laminaria cohorts (P = 0.001). A mean D&E theater time of 19 minutes for laminaria cohort A was reduced by 10.1% in the Dilapan-S cohort C (P = 0.02). The incidence of unscheduled overnight delivery outside the clinic was 0% for Dilapan-S and 1.3% for cohort A and 3.8% for cohort B laminaria cohorts (P = 0.14).Conclusion: Dilapan-S osmotic dilators are superior to laminaria in producing more cervical priming and dilatation in a shorter time. This enables 17–22 week D&E procedures to be carried out in fewer days and in shorter theater times. They also eliminate the risk of an unscheduled overnight delivery outside the clinic.Keywords: late second-trimester surgical abortion, dilatation and evacuation, cervical priming, osmotic dilators, Dilapan-S, laminaria tents